Calculation of the lattice constant of hexagonal compounds with two dimensional search of equation of state and with semilocal functionals a new package (2D-optimize) - Ali Hussain, Reshak, Prof. Dr.; Morteza, Jamal (Elsevier B.V., 2013)
Link to the publisher's homepage at http://www.elsevier.com/